Persepsi Penyuluh Pertanian Terhadap Internet di Kecamatan Sengah Temila dan Kecamatan Mandor - Fruticosa, Kornelinn; Prihtanti, Tinjung Mary (Universitas Galuh, 2024)
The agricultural sector has an important role in economic development, and the lives of people in Indonesia. Along with the rapid development of technology and science, it plays an important role in agricultural development. This study aims to describe the perception of agricultural extension workers towards the internet and the perception of extension workers towards the internet based on the characteristics of respondents. This research is a quantitative descriptive research. The sampling technique used saturated sampling or census. The sample of this study amounted to 37 agricultural extension workers in Sengah Temila District and Mandor District. This study shows that the perception of agricultural extension workers on the internet provides up to date information, is easy to reach, a means of obtaining complete information, a place to distribute information, and is easy to use and the perception of agricultural extension workers on the internet is high based on characteristics occurring in extension workers in Mandor District and Sengah Temila District aged 50-59 years, dominated by men, high school education level and work experience above 10 years.